Gene expression pattern of ESPL1, PTTG1 and PTTG1IP can potentially predict response to TKI first-line treatment of patients with newly diagnosed CML - Christiani, Eva; Naumann, Nicole; Weiß, Christel; Spiess, Birgit; Kleiner, Helga; Fabarius, Alice; Hofmann, Wolf-Karsten; Saußele, Susanne; Seifarth, Wolfgang (Cancers, 2023)
The achievement of major molecular response (MMR, BCR::ABL1 ≤ 0.1% IS) within the first year of treatment with tyrosine kinase inhibitors (TKI) is a milestone in the therapeutic management of patients with newly diagnosed chronic myeloid leukemia (CML). We analyzed the predictive value of gene expression levels of ESPL1/Separase, PTTG1/Securin and PTTG1IP/Securin interacting protein for MMR achievement within 12 months. Relative expression levels (normalized to GUSB) of ESPL1, PTTG1 and PTTG1IP in white blood cells of patients (responders n = 46, non-responders n = 51) at the time of diagnosis were comparatively analyzed by qRT-PCR. 3D scatter plot analysis combined with a distance analysis performed with respect to a commonly calculated centroid center resulted in a trend to larger distances for non-responders compared to the responder cohort (p = 0.0187). Logistic regression and analysis of maximum likelihood estimates revealed a positive correlation of distance (cut-off) with non-achieving MMR within 12 months (p = 0.0388, odds ratio 1.479, 95%CI: 1.020 to 2.143). Thus, 10% of the tested non-responders (cut-off ≥ 5.9) could have been predicted already at the time of diagnosis. Future scoring of ESPL1, PTTG1 and PTTG1IP transcript levels may be a helpful tool in risk stratification of CML patients before initiation of TKI first-line treatment.
Gesehen am 09.06.2023